Hydrogen production from herbal wastewater via anaerobic fermentation with diatomite‐immobilized sludge. Issue 1 (29th March 2021) - Liu, Ruina; Lin, Youwei; Xu, Gongdi; Li, Yongfeng
Abstract: The feasibility and performance of continuous hydrogen production from herbal wastewater via anaerobic fermentation was investigated at different organic loading rates (OLRs) (from 12 to 96 kg chemical oxygen demand [COD]·L −1 ·day −1 ) in diatomite‐immobilized sludge reactor and suspended sludge reactor. Results indicated that the diatomite‐immobilized sludge reactor presented more efficient and stable performance than suspended sludge reactor in terms of hydrogen production rate. In diatomite‐immobilized sludge reactor, the highest hydrogen production rate of 11.17 ± 0.45 mmol·L −1 ·h −1 was achieved at the optimum OLR of 72‐kg COD·L −1 ·day −1 . The metabolic route of acetate acid and butyrate acid production at low OLR (from 12‐ to 40‐kg COD·L −1 ·day −1 ) was modified to be ethanol production by an increase in OLR to 56 and 72‐kg COD·L −1 ·day −1, which was reflected by the distribution of bacterial community. The maximum energy recovery efficiency by dual production of hydrogen and ethanol was determined to be 31.2 kJ·L −1 ·h −1 at OLR of 72‐kg COD·L −1 ·day −1 .